2013
DOI: 10.1007/s00280-013-2160-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the potential effect of ponatinib on the QTc interval in patients with refractory hematological malignancies

Abstract: PurposeCardiac dysfunction, particularly QT interval prolongation, has been observed with tyrosine kinase inhibitors approved to treat chronic myeloid leukemia. This study examines the effects of ponatinib on cardiac repolarization in patients with refractory hematological malignancies enrolled in a phase 1 trial.MethodsElectrocardiograms (ECGs) were collected at 3 dose levels (30, 45, and 60 mg) at 6 time points. Electrocardiographic parameters, including QTc interval, were measured, and 11 morphological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 95%
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 95%
“…An in vitro assay conducted in human embryonic kidney cells stably expressing the hERG potassium channel revealed that ponatinib inhibits hERG at a concentration above 1 μM. 55 Vandetanib, a multi-kinase inhibitor approved for treatment of multiple cancer types, has been reported to inhibit the hERG at 3 μM detected by a whole-cell patch-clamp assay in transiently transfected HEK293 cells. 56 Finally, several new deephERG-predicted TKIs without literature data also need to be highly vigilant, such as bosutinib, gefitinib, afatinib and dasatinib, which are warranted by experimental or clinical validation in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the diagnosis was suggested only by echocardiogram in 5 of the 9 patients with this finding; catheterization was only performed (and confirmed the diagnosis) in 4 patients. The overall frequencies of vascular 5,[11][12][13][14][15][16][17][18]37 and cardiac [19][20][21][22][23][24][25][26] AEs varied across various clinical trials depending on the study design, type of TKI, treatment durations, AE definitions, and eligibility criteria. Contrary to some reports, 38 we observed that dasatinib was associated with a higher risk of AT-AE relative to imatinib, with a risk that appears similar to that with nilotinib.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-year probability of grade 3-4 cardiac, vascular, or congestive heart failure (CHF) AEs with imatinib was 0.5%, 0.3%, or 3.1%, respectively. 10 The relative frequencies of vascular 5,[11][12][13][14][15][16][17][18] and cardiac [19][20][21][22][23][24][25][26] AEs with the different TKIs are difficult to estimate based on the literature because different reports have used different methods for analysis, and what events are included in the general category of "arteriothrombotic events" vary widely, with some reports analyzing a few hundred medical dictionary for regulatory activities (MeDRA) terms while others focus only on specific confirmed diagnosis.…”
Section: Introductionmentioning
confidence: 99%